Association of spinopelvic alignment, lower extremity alignment, hamstring tightness, lower extremity range of motion with landing patterns in ballet dancers, folk dancers and football players - Aksu, N.; Atansay, V.; Akgonul, B.; Kara, A. N.; Hamzaoglu, A. (British Journal of Sports Medicine, 2021)
Background: Dancers are exposed to ACL injuries less than other athletes despite jumping more than other athletes. Objective: To reveal the differences between professional dancers and athletes by posture analysis (coronal and sagittal balances) using EOS X-ray-imaging system and landing patterns after jumps using Kinovea video analysis. Design Comparative study. Setting Professional folk and ballet dance groups and Premier League football players. Patients (or Participants): Volunteered 8 professional folk dancers, 8 professional ballet dancers and 8 premiere league football players. Interventions (or Assessment of Risk Factors): Hamstring tightness, increased pelvic incidence and thoracal kyphosis angles and decreased ROM are the risk factors for ACL injury during landing. Main Outcome Measurements: Hip, knee and ankle mean ROMs, SLR (straight leg raise) and frontal mechanical axis angle were significantly different between dancers group and athletes group (p<0.05). The mean P incidence angle and mean thoracal kyphosis angle in football players were significantly higher than dancer groups (p<0.05). Results: Folk dancers use heel, ballet dancers use forefoot and football players use midfoot landings at initial ground contact. Compared to dancers, football players have less trunk, hip, knee flexion degrees at initial ground contact on landing. Conclusions: Hamstring tightness, decreased lower extremity ROMs, trunk flexion, hip flexion, knee flexion during landing may increase ACL injury risk in football players. Optimal hamstring flexibility is very important for preventing injuries in football player, and it also helps athletes improve football-specific skills, such as sprinting, jumping, agility and kicking. These results support the rationale that muscle flexibility ought to be part of the specific training of football players.